Reserve options mechanism: The new monetary policy tool of CBRT and its effect on exchange rate volatility - Ibrahim Yasar Gok (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2016)
Purpose - Reserve Options Mechanism (ROM) is a new policy tool of Central Bank of the Republic of Turkey (CBRT). In this study, it is aimed to examine the effect of the ROM on USD/TL exchange rate volatility. Design/methodology/approach - The effects of the ROM and the direct foreign exchange interventions and auctions of CBRT on the USD/TL exchange rate volatility are analyzed by applying GARCH (1,1) model and using the data for the period 09.30.2011- 06.03.2016. Findings - It is found that the ROM significantly decreases the exchange rate volatility, which indicates the effectiveness of the ROM. The interventions of the CBRT also decrease the volatility but they do not play a significant role. Research limitations/implications - Although all available data for the ROM since the beginning of the mechanism are used, one of the limitations of the study is that the ROM and also the interventions of the CBRT are not the only explanatory variables for the USD/TL exchange rate volatility. However, the results imply that the ROM is an efficient policy tool and contributes to the financial stability. Originality/value - Since the ROM is introduced by CBRT recently, there are only a few empirical researches examining the effect of the ROM on exchange rate volatility. This study covers a longer and more recent time period than previous studies.
Keywords: E58; F31; G15; 330; Reserve Options Mechanism; Exchange Rate Volatility; CBRT; Financial Stability; GARCH